2009
DOI: 10.1007/s10620-009-0846-9
|View full text |Cite
|
Sign up to set email alerts
|

Significant Differences Between Crohn’s Disease and Ulcerative Colitis Regarding the Impact of Body Mass Index and Initial Disease Activity on Responsiveness to Azathioprine: Results from a European Multicenter Study in 1,176 Patients

Abstract: In a survey comprising 1,176 patients with inflammatory bowel disease (IBD) we recently showed that azathioprine (AZA) beyond 4 years is beneficial in ulcerative colitis (UC) patients and in a subset of Crohn's disease (CD) patients. Here, we show for the first time that azathioprine responsiveness depends on body mass index (BMI). The relationship is reciprocal in UC and CD, with a better outcome in UC patients with a BMI<25 and in CD patients with a BMI>25. These observations are particularly interesting con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Furthermore, a case report suggested that reducing body weight might also contribute to decreasing disease activity in UC [32]. Holtmann et al [33] have also recently shown improved outcomes after azathioprine treatment in UC patients with BMI maintained under 25, suggesting the benefit of body weight control in IBD patients. The results from our study emphasize the importance of lifestyle modifications, such as regular exercise, body weight reduction, and smoking cessation, not only in the general population, but also in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a case report suggested that reducing body weight might also contribute to decreasing disease activity in UC [32]. Holtmann et al [33] have also recently shown improved outcomes after azathioprine treatment in UC patients with BMI maintained under 25, suggesting the benefit of body weight control in IBD patients. The results from our study emphasize the importance of lifestyle modifications, such as regular exercise, body weight reduction, and smoking cessation, not only in the general population, but also in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…25 This study used the ACD as a surrogate for disease severity. Higher daily dose of mesalazine (4.8 g/d) is indicated in moderate disease, whereas lower dose (2.4 g/d) is enough for mild disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Holtmann et al [36] were able to show that in UC, patients with a BMI of \ 25 respond better to azathioprine than patients with a BMI [ 25. In CD, the response to azathioprine is independent from the BMI during treatment with azathioprine. This is slightly different from our findings.…”
Section: Discussionmentioning
confidence: 99%